ANALISIS PENGARUH SUMBER DAYA FINANSIAL, KOGNITIF DAN EMOSIONAL KONSUMEN TERHADAP KUALITAS LAYANAN PELANGGAN PADA PT SERASI AUTORAYA (TRAC – ASTRA RENT A CAR) CABANG KALTENGSEL - Jarwo, Sujarwo (Jurnal Ilmiah Ekonomi Bisnis, 2023)
Abstract: The impact of the development of the automotive industry and the transportation equipment rental system has increased competition in the car rental business in Indonesia. Companies that are able to provide good quality customer service will be able to win business competition and will be chosen by consumers to use vehicle rental services. PT Serasi Autoraya (TRAC Astra Rent A Car) Kaltengsel Branch is a rental company that always pays attention to the quality of customer service. Service quality perceived by consumers is influenced by financial, cognitive and emotional resources of consumers. The purpose of this study was to determine the effect of consumers' financial, cognitive and emotional resources on the quality of customer service at PT Serasi Autoraya (TRAC Astra Rent A Car) Kaltengsel Branch, as well as provide suggestions and input regarding the resources owned by customers so that they can be responded to by company to provide quality and satisfactory customer service. The population used in this study were customers from PT Serasi Autoraya (TRAC Astra Rent A Car) Kaltengsel Branch. The sample in this study was 100 respondents determined by the slovin formula. The method used in this study is a quantitative method using SPSS. The results of the study show that the financial, cognitive and emotional resources of consumers simultaneously have a significant effect on the quality of customer service. And the most influential variable is consumer emotion. Keywords: Financial Resources, Cognitive, Emotional Consumers, Quality of Service, TRAC Astra Rent A Car